An analysis of Islamic banks' exposure to rate of return risk - Zainol, Zairy; Kassim, Salina (The Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC), 2010)
The objective of this study is to analyze the dynamic effects of interest rate changes on the rate of return of Islamic banks and the amount of deposits in the conventional and Islamic banks. In analyzing the potential rate of return risk in the Islamic banks and interest rate risk in the conventional banks, for the Islamic banks, the 3-month Islamic deposit rate of return and total Islamic deposit are considered, while for the conventional banks, the 3-month fixed deposit interest rate and total conventional deposits are considered. Using data covering the period from January 1997 to October 2008, the study applies the cointegration analysis, bi-variate Granger causality test, Impulse Response Function (IRF) and Variance Decomposition (VDC) analysis based on the Vector Auto-regression (VAR) framework. The results of the study have important implications on the risk management practices of the Islamic banks in Malaysia. Several suggestions are put forward to mitigate the rate of return risk so as to ensure healthy growth of the Islamic banking institutions.